Magnetoreception and magnetic navigation in fishes: a half century of discovery - Naisbett-Jones, Lewis C.; Lohmann, Kenneth J. (Journal of Comparative Physiology, 2022)
As the largest and most diverse vertebrate group on the planet, fishes have evolved an impressive array of sensory abilities to overcome the challenges associated with navigating the aquatic realm. Among these, the ability to detect Earth’s magnetic field, or magnetoreception, is phylogenetically widespread and used by fish to guide movements over a wide range of spatial scales ranging from local movements to transoceanic migrations. A proliferation of recent studies, particularly in salmonids, has revealed that fish can exploit Earth’s magnetic field not only as a source of directional information for maintaining consistent headings, but also as a kind of map for determining location at sea and for returning to natal areas. Despite significant advances, much about magnetoreception in fishes remains enigmatic. How fish detect magnetic fields remains unknown and our understanding of the evolutionary origins of vertebrate magnetoreception would benefit greatly from studies that include a wider array of fish taxa. The rich diversity of life-history characteristics that fishes exhibit, the wide variety of environments they inhabit, and their suitability for manipulative studies, make fishes promising subjects for magnetoreception studies.